Streets for exchange a restructuring of the inner city: Johannesburg - English, Larry (My University, 1993)
Johannesburg's inner-city is in crisis. Physically; the city is deteriorating. Daily, the media reports of increased crime figures, and yet another corporation moving to suburbia. Institutions which remain in the city intensify their security and offer internalised canteens, gymnasiums and parking to their staff so that they need not venture out onto the streets. It is therefore doubtful that institutions which remain do so out of love for the city; rather, it would appear that these decisions are motivated for reasons of retaining their property investments. In reaction. city politicians (who live in suburbia) have embarked on cosmetic urban design upgrades and programmes to keep Johannesburg clean, or green, while others campaign for transportation solutions and stadiums driven by manifestos to make Johannesburg a truly 'world' city - Eurocentric images of what great cities should be. [No abstract provided. Information taken from introduction].
This discourse is submitted to the Faculty of Architecture, University of the Witwatersrand, Johannesburg, in partial fulfilment of the degree Master of Urban Design, Johannesburg, October 1993
Keywords: City planning--South Africa--Johannesburg; Urban policy--South Africa--Johannesburg